2019
DOI: 10.1159/000496663
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Management of Patients with Heart Failure within Asia-Pacific, Middle East, and African Countries: A Toolbox for Healthcare Providers

Abstract: Objectives: The management of heart failure (HF) is most effective when established treatment guidelines and recommendations are followed. We aimed to develop a “Toolbox” of resources to facilitate the care of patients with acute HF and chronic HF with reduced ejection fraction delivered by healthcare professionals across Asia-Pacific, the Middle East and Africa (henceforth referred to as the “Region”). Methods: We convened a group of cardiologists from across the Region to develop a set of checklists, algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For instance, although HF management guidelines from the USA, Canadian, Australia, Europe and South Asia all recommend dedicated HF follow‐up within 7–14 days post discharge, they do not specify the setting (i.e. HFC vs. primary care) where follow‐up should take place 3–7 . This likely reflects the fact that HFCs may not readily available or accessible in all regions and countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, although HF management guidelines from the USA, Canadian, Australia, Europe and South Asia all recommend dedicated HF follow‐up within 7–14 days post discharge, they do not specify the setting (i.e. HFC vs. primary care) where follow‐up should take place 3–7 . This likely reflects the fact that HFCs may not readily available or accessible in all regions and countries.…”
Section: Discussionmentioning
confidence: 99%
“…HFC vs. primary care) where follow-up should take place. [3][4][5][6][7] This likely reflects the fact that HFCs may not readily available or accessible in all regions and countries. We accounted for this through an inclusive search strategy, as well as including patients referred to internists and geriatricians.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the eleven studies on HF in Lebanon reported sociodemographic characteristics of the study participants; eight studies reported select clinical and medical characteristics. Excluded papers reported the development of a culturally appropriate intervention in the Lebanese context , a suggestion for an HF toolbox (Kabbani et al, 2019), and an article that discussed electrocardiogram determinants (Khalil et al, 2016) without details on HF. Matta et al's (2016) study reported a single case with limited findings and was thus excluded.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…10 The checklists currently available are American College of Cardiology (ACC) consensus, 12 Target HF checklist, 13 Heart Failure Checklist from National Heart, Singapore, 14 All India Institute of Medical Sciences (AIIMS) HF critical care unit Checklist, 9 ABCD checklist, 9 HF passport (Hriday Card), 9 and HF Toolbox. 15 …”
Section: Introductionmentioning
confidence: 99%